Abuzul asupra copilului - Bonea, Georgiana-Virginia (Calitatea Vieții, 2017)
This paper’s main objective is to list and analyze various forms of child abuse and their short-, medium- and long-term consequences. Child abuse currently represents one of the largest and most important fields of contemporary study. Romania has adopted most of the European Union’s legislation for fighting and preventing abuse against minors. Furthermore, services offered by the Romanian state as well as state-accredited NGOs are increasingly aimed at preventing abuse through multiple campaigns of informing the public about the lasting negative consequences of abuse against children.